Enhanced Reactivity of Water Clusters towards Oxidation in Water/Acetonitrile Mixtures. Issue 12 (17th June 2016) - Hidalgo‐Acosta, Jonnathan C.; Scanlon, Micheál D.; Méndez, Manuel A.; Peljo, Pekka; Opallo, Marcin; Girault, Hubert H.
Abstract: The water oxidation process in acidified water/acetonitrile mixtures was studied by cyclic voltammetry using fluorinated tin oxide (FTO) electrodes modified layer‐by‐layer with deposited bilayers of positively charged poly(diallyldimethylammonium chloride) (PDDA) polymer and negatively charged citrate‐stabilized iridium oxide (IrO2 ) nanoparticles. The voltammetric profiles obtained at high water contents resemble those in aqueous media and remain approximately unchanged. However, as the water content decreases below a water mole fraction ( X H2 O) of 0.6, a tipping point is reached and the onset potential for water oxidation gradually decreases. This reflects an enhanced reactivity, and therefore lower overpotential, of water molecules towards oxidation in water/acetonitrile mixtures. These lower kinetic barriers towards water oxidation are rationalized based on the degradation of the hydrogen bond network upon the formation of water/acetonitrile mixtures. Thus, as the ice‐like structure of neat water transitions to clusters and low‐bonded oligomers, these water molecules in more "free" states exhibit an enhanced susceptibility to water oxidation. Abstract : Divided we fall : Cyclic voltammetry studies show that water in water/acetonitrile mixtures is more easily oxidized due to the weakening of the intermolecular hydrogen bond network of the water.